Upaya Peningkatan Pembelajaran Gerak Dasar Tolak Peluru dengan Menggunakan Modifikasi Alat pada Siswa Kelas VII SMP Negeri 2 Pekanbaru - Balqis Amirah Adli; Agus Sulastio; Siti Maesaroh; Muhammad Imam Rahmatullah; Melina Pabila Rina Ayu (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
One way that physical education instructors might improve learning results is by creating bulletproof media. This study modifications made to the bullet-repelling tool as well as the efficacy of using the modified tool. Modified tools have been tested with outcomes that will be discussed in the findings of explanations and sub-explanatory talks. These modified tools are evaluated by material experts and media experts. A test of the bullet repulsion's efficiency was also conducted after the results on the most suitable modification tool that could be employed. The instructor and pupils of class VII of SMPN 2 Pekanbaru are conducting the study project. The instructor and pupils of class VII of SMPN 2 Pekanbaru are conducting the study project. Qualitative research is the kind of study that is modified. Classroom action research, often known as CAR, is the study methodology used. In this study, observation, literary analysis, documentation, and evaluation. Based on the findings of study and data analysis, the fundamental mobility of students at SMP Negeri 2 Pekanbaru who are bulletproof has improved. Keywords: shot put 1, Tool Modification 2, Learning 3